Tourist perceptions in the quality of sustainable tourism services in Lombok - Eka Female Patrecia Manihuruk; Maria Lupita Sari (Journal of Rural Tourism, 2024)
Purpose - The purpose of this study is to measure tourists' perceptions of the quality of sustainable tourism services in Lombok and analyze which dimensions of service quality most influence tourist satisfaction. Methodology/Design/Approach - The study involves both domestic and foreign tourists, analyzing their perceptions of sustainable tourism services. It examines various dimensions of service quality, including environmental sustainability, local wisdom, and facilities, to understand their impact on tourist satisfaction. Finding - The study found that tourists highly value environmental sustainability, local wisdom, and the quality of facilities. These factors significantly influence their satisfaction with sustainable tourism services in Lombok.Originality/Value - This research provides valuable insights into how sustainable tourism practices, particularly those focused on environmental and cultural aspects, contribute to tourist satisfaction. It emphasizes the importance of incorporating local wisdom and quality facilities into sustainable tourism development to enhance the overall visitor experience in Lombok.